Posthuman Pedagogies in Practice Arts based Approaches for Developing Participatory Futures - Bayley, Annouchka (Springer International Publishing, 2018)
This book investigates transdisciplinary, arts-based approaches to developing innovative and pertinent higher education pedagogy. Introducing timely critical thinking strategies, the author addresses some of the key issues facing educators today in an increasingly complex digital, technological and ecological world. The author combines emerging ideas in the New Materialism and Posthumanism schools of thought with arts-based teaching and learning, including Practice-as-Research, for Social Science contexts, thus exploring how this approach can be used to productively create new pedagogical strategies. Drawing on a rich repertoire of real-life examples, the volume suggests transferrable routes into practice that are suitable for lecturers, researchers and students. This practical and innovative volume will appeal to researchers and practitioners interested in Posthuman and New Materialist theories, and how these can be applied to the educational landscape in future.